2014
DOI: 10.1039/c4mb00319e
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin 3-O-rutinoside mediated inhibition of PBP2a: computational and experimental evidence to its anti-MRSA activity

Abstract: The PBP2a is a cell wall synthesizing protein, which causes resistivity in methicillin resistant Staphylococcus aureus (MRSA) from β-lactam antibiotics but it is susceptible to 5th generation cephalosporin, ceftobiprole. Ceftobiprole inhibits the growth of MRSA by targeting the PBP2a-mediated cell wall synthesis, but it is reported to have adverse side effects. Due to this, there is a constant need to develop natural alternatives, which are generally free from adverse side effects. Hence in this study, in sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…[28] Quercetin demonstrated the highest inhibition potential toward PBP2a with a binding energy of −10.0 kcal/mol. It is notable that quercetin derivatives have already been reported to have antibacterial activity against MRSA bacteria by Rani et al [29] Since quercetin derivatives have already been proven for their in vitro anti-MRSA and anti-PBP2a activity, it supports the current prediction of quercetin being inhibitor of PBP2a. Inhibition of PBP2a would result in bactericidal activity, by disruption of the biosynthesis of bacterial cell wall.…”
Section: Discussionsupporting
confidence: 69%
“…[28] Quercetin demonstrated the highest inhibition potential toward PBP2a with a binding energy of −10.0 kcal/mol. It is notable that quercetin derivatives have already been reported to have antibacterial activity against MRSA bacteria by Rani et al [29] Since quercetin derivatives have already been proven for their in vitro anti-MRSA and anti-PBP2a activity, it supports the current prediction of quercetin being inhibitor of PBP2a. Inhibition of PBP2a would result in bactericidal activity, by disruption of the biosynthesis of bacterial cell wall.…”
Section: Discussionsupporting
confidence: 69%
“…Because natural compounds are considered to be safe, nontoxic, and less prone to side effects (Rani et al, 2014 ), in the present study, naturally occurring phytochemicals from different plant sources were selected and validated for PBP2a inhibition in MRSA infection. Molecular docking analysis suggested that diferulic acid had a higher specificity toward the PBP2a binding site and thus caused inhibition of MRSA by inhibiting the biosynthesis of its cell wall (Rani et al, 2014 ). It is notable that the compound taxifolin exhibited antibacterial activity by hindering with the function of ERM in MLSB strains of S. aureus .…”
Section: Resultsmentioning
confidence: 99%
“…[30] Quercetin rutinoside detected in extract of Ajwa has been widely reported for their antibacterial activity. Rani et al [31] reveled the antibacterial potential of Quercetin 3-O-rutinoside against Staphylococcus aureus and they also observed changes in bacterial colonies and surface. Likewise, Alvarez et al, [32] also observed the antibacterial effect of quercitin-rutinoside against Staphylococcus aureus, Escherichia coli, and Enterobacter aerogenes.…”
Section: Resultsmentioning
confidence: 99%